Internal quality of eggs coated with whey protein concentrate - Ana Cláudia Carraro Alleoni; Aloísio José Antunes (Scientia Agricola, 2004)
The functional properties of foods can be preserved when they are coated with edible films, since both the loss of moisture and the transport of O2 and CO2 are reduced. The objectives of this work were: to compare weight loss, Haugh units, and albumen pH between fresh eggs and eggs coated with whey protein concentrate (WPC), under six storage periods (3, 7, 10, 14, 21 and 28 days), at 25°C. During the entire storage period, regardless of whether the eggs were coated or not, the Haugh unit values and the weight loss decreased, and differences between values from the first to the last period were lower for coated eggs. Albumen pH increased. The Haugh unit values for coated eggs were similar to those found in literature references when the same storage period was considered.